A note on diatom stratigraphic markers in upper Miocene sediments of the Pisco Formation, Peru, and description of Delphineis urbinai sp. nov. Issue 3 (2nd July 2016) - Gariboldi, Karen
Abstract : With the aim of preparing the ground for a comprehensive stratigraphic work on the Mio-Pliocene Pisco Formation, Peru, diatom marker species from the upper Miocene sites of Cerro Colorado (CC) and Cerro Los Quesos (CLQ) were investigated. Samples were collected along two composite stratigraphic sections and prepared for microscope analysis. Marker species are listed and described; their ranges and taxonomy are discussed in the light of recent works on Pacific diatom biostratigraphy and compared to findings in previous works from the 1980s on the Pisco Formation. Subsequently, marker species ranges and taxonomy have been significantly revised, suggesting that age-attributions based on sediments of the Pisco Formation should also be corrected. Examples are: (1) Koizumia tatsunokuchiensis, which was known as a Pliocene marker, but is now known to first appear in the late Miocene; (2) Thalassiosira cf. flexuosa, which was reported in early works on the Pisco Formation biostratigraphy as Coscinodiscus plicatus ; (3) Thalassiora antiqua, which is found both at CC and CLQ, although typical of cold waters. The need to build a specific diatom biozonation for this Pacific region is thus highlighted. In addition, a new species, Delphineis urbinai, is described. This species is not a biostratigraphic marker but its sporadic presence may help with the correlation of stratigraphic sections within the Pisco Formation.